A) 4/5 + 3/4 + 2/3 + (1/3)² + (1/4 + 1/5)² =
b) 9/8 + (1/4 - 1/2)² + (1/8+1)² =
c) (1/4-1)² × (1 - 1/5)³ x (1/6 - 1)² x (1 - 1/3)³ =
d) 0,75² - 5/6 - 1/2 =
e) 2/3 - 5/7 - (1 1/3)² =
f) (0,6 - 1/3 + 0,25) =
g) 4/5 - (0,75+1,2) ² =

e) ...(1 1/3)...=jeden i jedna trzecia

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-10-31T22:04:39+01:00
B) 9/8 + (1/4 - 1/2)² + (1/8+1)² =9/8+(-¼)²+(9/8)²=9/8+1/16+81/64=72/64+4/64+81/64=157/64=2 29/64

c) (1/4-1)² × (1 - 1/5)³ x (1/6 - 1)² x (1 - 1/3)³ =(-3/4)² x(4/5)³ x(-5/6)² x(2/3)³=9/16 x 64/125 x 25/36 x 8/27=8/81

d) 0,75² - 5/6 - 1/2 =9/16-5/6-8/16=1/16-5/6=6/96-80/96=-74/96=-37/48

e) 2/3 - 5/7 - (1 1/3)² =2/3-5/7-16/9=42/63-45/63-112/63=-115/63=-1 52/63

2 3 2
  • Igo
  • Rozwiązujący
2009-10-31T22:17:47+01:00
A) 4/5 + 3/4 + 2/3 + (1/3)² + (1/4 + 1/5)² = 4/5 + 3/4 + 2/3 +1/9 + [(1/4)² + 2*1/4*1/5 +(1/5)²] = 4/5 + 3/4 + 2/3 +1/9 + 1/16 + 1/10 + 1/25 = 2,5302777

b) 9/8 + (1/4 - 1/2)² + (1/8+1)² = 9/8 + [(1/4)² - 2*1/4*1/2 + (1/2)²] + [(1/8)² + 2*1/8*1 + 1²] = 9/8 + (1/16 - 1/4 + 1/4) + (1/64 + 1/4 + 1) = 9/8 + 1/16 + 17/64 + 1= 2 i 29/64

c) ...
d) 0,75² - 5/6 - 1/2 = 0,5625 - 5/6 - 1/2 = -0,770833
e) 2/3 - 5/7 - (1 1/3)² = 2/3 - 5/7 - 1 7/9 = -1 59/63
f) (0,6 - 1/3 + 0,25) = 0,51(6)
g) 4/5 - (0,75+1,2) ² = 4/5 - [(0,75)² + 2*0,75*1,2 + (1,2)² = 4/5 - (0,5625 + 1/8 + 1,44) = 4/5 + 2,1275 = 2,9275

Wyniki z kalkulatora sama oceń czy dobrze ;P